The effect of Corporate Social Responsibility, Capital Intensity and Managerial Ownership on Tax Avoidance at Mining Company - Herianti, Eva; Setia Budi, Agung (Journal of Applied Management and Business, 2024)
The objective of this study is to analyze and examine the effect of corporate social responsibility, capital intensity, and managerial ownership on tax avoidance in mining companies listed on the Indonesian stock exchange. The sample was processed with purposive sampling technique, amounting 72 respondents were obtained from mining companies in the oil, gas and coal subsectors at www.idx.co.id for the period 2020-2022. The research method used is quantitative method with panel data regression as a data analysis technique. The results of this study demonstrate that corporate social responsibility, capital intensity, and managerial ownership simultaneously affect tax avoidance. Corporate social responsibility and capital intensity partially have a significant and negative effect on tax avoidance. Meanwhile, managerial ownership has no effect on tax avoidance.